2016
DOI: 10.3892/ol.2016.5354
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses the proliferation of gastric cancer cells by downregulating H19

Abstract: Curcumin, a major phytochemical in turmeric, inhibits the proliferation of many types of solid cancer cells by enhancing p53 expression. However, the long non-coding RNA H19 directly inhibits p53 activation and thus promotes gastric cancer progression. The aim of this study was to assess the role of H19 in curcumin-induced proliferative inhibition of gastric cancer. The gastric cancer cell line SGC-7901 was treated with curcumin at different concentrations and time points. The effect of curcumin on proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 48 publications
2
43
0
2
Order By: Relevance
“…26 Curcumin inhibits the expression of lncRNA H19 in a concentration-dependent manner, and its ectopic expression reverses curcumin-induced cell apoptosis and decreases p53 expression. 28 The lncRNA MALAT1 serves as a potential marker of survival in stage 1 NSCLC patients and is downregulated following resveratrol treatment. 202 It has been reported that the expression of a total of 538 lncRNAs can be reversed by treatment with berberine, 203 indicating that the global effect of berberine is to modulate lncRNA expression.…”
Section: Noncoding Rna Regulationmentioning
confidence: 99%
“…26 Curcumin inhibits the expression of lncRNA H19 in a concentration-dependent manner, and its ectopic expression reverses curcumin-induced cell apoptosis and decreases p53 expression. 28 The lncRNA MALAT1 serves as a potential marker of survival in stage 1 NSCLC patients and is downregulated following resveratrol treatment. 202 It has been reported that the expression of a total of 538 lncRNAs can be reversed by treatment with berberine, 203 indicating that the global effect of berberine is to modulate lncRNA expression.…”
Section: Noncoding Rna Regulationmentioning
confidence: 99%
“…It reduced liver fat in patients with nonalcoholic fatty liver disease (Rahmani et al, ). Curcumin as anticancer agent (Allegra et al, ) has good effects in head and neck squamous cell carcinoma (Wilken, Veena, Wang, & Srivatsan, ), and also, it is effective in suppressing gastric, colon, and breast cancer (Banik, Parasuraman, Adhikary, & Othman, ; Khosropanah et al, ; Liu, Xiang, Wu, & Wang, ; Tong, Wang, Sun, & Suo, ). It has preventive effects on tobacco smoke‐induced liver cancer (Liang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that p53, which is described as a ‘tumor suppressor’, regulates a variety of apoptotic signals in SGC-7901 cell ( 32 , 33 ). Bcl-2, an anti-apoptosis molecule, serves a critical function in controlling apoptosis ( 34 ). Caspase-3, classified as an executioner, mediates the final process of cell death ( 35 ).…”
Section: Discussionmentioning
confidence: 99%